Proper Calibration of Soil Fumigant Application Equipment - Joseph w. Noling (EDIS)
Calibration of soil fumigant equipment and determination of soil fumigant application rate are two of the most important factors contributing to the success or failure of pest control efficacy and crop production response, yet generate some of the greatest confusion among many researchers and growers alike. This 5-page fact sheet was written by J.W. Noling and published by the UF Department of Entomology and Nematology, December 2012.